Chloride release characteristics of desulfurization wastewater droplet during evaporation process using the single droplet drying method. (1st December 2021) - Chen, Heng; Zhan, Lingxiao; Gu, Liyan; Feng, Qianyuan; Zhao, Ning; Feng, Yongxin; Wu, Hao; Yang, Linjun
Graphical abstract: Highlights: Chloride release characteristics were investigated by the single droplet drying method. The release process could be distinguished into three periods. It accounts for 66% of the total release chloride in the unstable shell stage. The release characteristics were mainly affected by droplet temperatures and shell formation. Abstract: The desulfurization wastewater evaporation technology is an effective way to realize zero-liquid discharge (ZLD). However, the release of chloride during the evaporation process is still a great challenge, which may cause severe chloride enrichment in the wastewater. In this work, the single droplet drying (SDD) method was utilized to investigate the chloride release characteristics during the evaporation process. The three periods of chloride release were first proposed based on the chloride release ratio and wastewater droplet's features (mass, temperature, and diameter). With the removal of the free moisture, the first period (Free water evaporation) was initiated, and almost no released chloride was detected; In the unstable shell period, 19.8% chloride would release there, mainly due to the increased droplet's temperature; Approximately 10% chloride would release during the shell pyrolysis period, which was directly related to the hydrolysis of the chloride-based salt hydrates in the evaporation particle. Besides, the chloride release characteristics at different cations species and ambient temperature were investigated. The desulfurization wastewater with a higher Mg 2+ concentration would be more likely to release chloride during the evaporation process. With the temperature increased from 150 to 300℃, the chloride release ratio would improve from 14.56 to 29.8% due to the disruption of the shell and the hydrolysis degree at a higher temperature. In practical engineering practices, a balance point between chloride release and evaporation efficiency should be found, and the Mg 2+ in the wastewater should be pre-treated before entering into the evaporation system.